Law and innovation in new resistant grapevine varieties - John Barker (Wine Economics and Policy, 2017)
This article is a brief account of the main laws governing or impacting upon the breeding of new resistant grapevine varieties, complementing previous work in this Journal. It focusses on the emergence of the legal fields of plant variety rights and sanitary and phytosanitary measures to bring law into the foreground as an important set of institutional parameters which shapes the actions of economic operators involved in the development of new resistant grapevine varieties in both direct and contingent ways.
Keywords: 330; Law; Plant variety rights; Sanitary and phytosanitary measures